PROTEIN UTILIZATION BY BROILER CHICKENS FED THREE COMMERCIAL PREMIXES (1990)
Three feeding trials, the first of nine weeks duration, the second and third of ten weeks duration each were carried out to investigate the protein utilisation by broiler chicks fed three premixes. In the first trial three diets with different premixes were fed to the broiler chickens. The premixes used sanders broiler starter and finisher premix (premix 3), Roche zoodry broiler premix (premix R) and Dizengoff vitadiz B.P (premix D). The starter rations contained 23% crude protein and energy level of 2970 Kcal ME/kg diet. The finisher rations contained 20% crude protein and energy level of 2940 Kcal ME/kg diet. Records of average weekly live weight, feed intake and body weight gain; feed conversion ratio, body weight gain per gram protein intake were taken, while the dry matter digestibility, nitrogen digestibility and nitrogen retention trials were carried out at the fourth and eighth weeks. There were significant differences (P<.0.05) in ail parameters tested except in the dry matter digestibility coefficient. Birds fed premix S and those fed premix R had the best performances. In the second trial the premixes used were the same as in the first experiment. At the starter phase the birds were divided into three dietary treatments based on different premixes. All the diets had 23% crude protein and the energy level was 2970 Kcal ME/kg diet. The birds fed the different premixes showed significant differences (P<0.05) in their average weekly live weight, feed intake, and body weight gain; feed conversion ratio, dry matter digestibility coefficient, carcass trait, weights of wings, back, breast, total edible meat and total bore; crude protein content (dry natter basis) of organs, blood glucose, liver glutamate oxaloacetate transaminase (LGOT) and liver xanthine dehydrogenase. Birds fed premix S and those fed premix R had the best feed utilization and carcass characteristics. For the finisher phase each of the three treatments of the starter phase was further divided into three, and the three treatments of a finisher phase obtained from a single treatment of the starter phase were allocated to three different premixes. Thus there was a total of nine treatments at the finisher phase. All the diets contained 20% crude protein and the energy level was 2940 Kcal ME/kg diet. The birds fed the different diets showed significant differences (P<0.05) in all parameters except in their nitrogen retention, weights of spleen, lungs, breast, abdominal fat, and total hone, blood glucose, plasma albumin, plasma globulin, serum total protein, serum albumin, serum creatine and LGCT. Birds fed premix S at the starter and finisher phases had the best feed utilization and carcass characteristics. In the third trial the premixes used were the same as in trials one and two. At the starter phase the experiment was designed so that the diets contained three different premixes with two levels of palm oil (1% and 2%). There was a total of six dietary treatments. All the diets were isocaloric (about 3000 Kcal/Ag diet) and isonitrogenous (23% crude protein) . The birds fed the different premixes showed significant differences (F<0.05) in ail the parameters tested except in the average weekly body weight gain, dry natter digestibility coefficient, weights of feathers, viscera, liver, spleen, kidney, lungs, abdominal fat and total bone; blood urea nitrogen, plasma components, serum total protein, globulin, uric acid, creatine, and creatinine; and LGCT, Birds fed premix R with 1% or 2% oil and birds fed premix S with 2% oil had better feed utilization while birds fed premix R with 1% or 2% oil had the beat nitrogen retention and carcass characteristics. For the finisher phase each of the six treatments of the starter phase vas divided into three, and the three treatments of the finisher phase obtained from a single treatment of the starter phase were allocated to the three premixes, thus making a total of eighteen treatments at the finisher phase. All the diets were Isocaloric and Isonitrogenous. Birds fed the different premixes showed significant (P< 0.05) differences in all parameters measured except in their total nitrogen output, nitrogen retention (grams), plasma globulin, serum globulin and serum creatine. Birds fed premix R at the starter and finisher phases with 2% oil had the best feed utilization and carcass characteristics. It was concluded that premix S and premix R gave satisfactory results in respect of broiler feed utilization, nitrogen retention and carcass characteristics, when fed throughout at the starter and finisher phases or interchangeably at the starter and finisher phase, with or without palm oil. However 2% palm oil can be added to improve the performance of the birds. The need for establishing appropriate combinations of premixes to be used for broiler production in Nigeria was highlighted, it was also suggested that standards be established for the premixes used in Nigeria.